TRAINING OF STRAW EKSPLORATION TO ART STATUE IN MARTAPURA OGAN KOMERING ULU TIMUR, SOUTH SUMATRA - Mubarat, Husni; Ilhaq, Mukhsin (Institut Seni Indonesia Padangpanjang, 2019)
The training of straw sculpture in East Ogan Komering Ulu (OKU) is an effort to provide education and experience to the community that does not have the creativity in exploring straw into sculpture works. This training is a straw festival activity with the theme